2002
DOI: 10.1016/s0969-806x(01)00574-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of γ-irradiation to produce films from whey, casein and soya proteins: structure and functionals characteristics

Abstract: g-irradiation and thermal treatments have been used to produce sterilized cross-linked films. Formulations containing variable concentrations of calcium caseinate and whey proteins (whey protein isolate (WPI) and commercial whey protein concentrate) or mixture of soya protein isolate (SPI) with WPI was investigated on the physico-chemical properties of these films. Results showed that the mechanical properties of cross-linked films improved significantly the puncture strength for all types of films. Size-exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(52 citation statements)
references
References 8 publications
2
47
0
1
Order By: Relevance
“…However, decrease in the solubility of protein observed in current study is in agreement with the results of Abu et al (2006) and Lacroixa et al (2002) who demonstrated gamma irradiation decreased protein solubility due to denaturation occurring through cross-linking of chains and protein aggregation. Moreover, treatment of canola meal with gamma irradiation was successful in reducing degradation of protein by rumen microorganisms and increasing intestinal digestibility of feed protein (Shawrang et al, 2008).…”
Section: Resultssupporting
confidence: 93%
“…However, decrease in the solubility of protein observed in current study is in agreement with the results of Abu et al (2006) and Lacroixa et al (2002) who demonstrated gamma irradiation decreased protein solubility due to denaturation occurring through cross-linking of chains and protein aggregation. Moreover, treatment of canola meal with gamma irradiation was successful in reducing degradation of protein by rumen microorganisms and increasing intestinal digestibility of feed protein (Shawrang et al, 2008).…”
Section: Resultssupporting
confidence: 93%
“…5,7 Some authors have studied the effects of processing variables, such as type and content of plasticizers, and storage conditions (relative humidity and temperature) on rheological, mechanical, thermal and functional properties of sodium caseinate films. 1,5,7,8 Other publications have been focused on the addition of different polymers such as starch, 9,10 whey protein isolate (WPI), soy protein isolate (SPI), 6,11 or gelatin 12,13 to caseinate films in order to improve physical, barrier, and solubility properties. flexibility and processability) or to add functionality to films.…”
Section: Introductionmentioning
confidence: 99%
“…This arises from the fact that both these processes result in the creation of crosslinks between the protein chains, although irradiation appears more effective in the case of caseinates or soya proteins, while heating is more effective in the case of globular milk proteins containing high amounts of lactoglobulins (whey protein isolate (WPI) and whey protein concentrate). 14,16 Previous studies have also shown that using a mixed composition containing calcium caseinate (CC) with WPI, accompanied by the appropriate combination of irradiation and heating, enables the production of films with higher tensile strength and lower permeability to water vapor than using each protein alone. 17 It was, moreover, discovered that the addition of a small amount of polysaccharide (carboxymethylcellulose, pectin, agar) to the film composition (at a level of 50 g kg −1 of protein) may facilitate production of films characterized by good barrier properties and high mechanical resistance.…”
Section: Introductionmentioning
confidence: 99%
“…13,20 A denser protein network with a larger content of β-strands and β-sheets was detected in irradiated and/or heated proteins than in reference proteins. 13,16,22 The changed protein conformation is expected to alter other physicochemical properties apart from the functional properties of the films. On the other hand, the changes in physicochemical properties of solutions, gels and films deliver important information concerning modification of the polymer structure.…”
Section: Introductionmentioning
confidence: 99%